Design and Application of an Elephant Trunk-like Spiral Deployable Mechanism - Wang Rugui; Jin Cong; Yang Zehui (Jixie chuandong)
Based on the two postures of trunk roll-up and extension, a spiral spatial folding mechanism composed of multiple modules is designed. The geometric relationship between the modules is analyzed, and the endpoint positions of the modules are calculated by the D-H method. The influence of the angle, length, number and scaling factor of the modules on the spiral shape is discussed. The spiral shape is designed as a whole by dimensional optimization, and the design of the solar wing is used as an example to calculate the dimensional parameters with the maximum unfolding length as the objective function and the spiral range, spacing and rod size as the constraints. The 3D models of the solar wing and gripper applications are given, and the appropriate driving method is briefly described for each application. This mechanism has a wide range of applications and can provide some reference for the design of the spiral mechanism.